Plasma Needles on the Teeth Structure and Compressibility - Hussein, Mohammed (Arab Journal for Sciences and Research Publishing, 2016)
The aim from this research is to prove not affected the teeth of both damage macroscopic and the internal structure of teeth (compressibility). The teeth were collected from (Al karama dental specialized) in Baghdad, directly after uprooted from the patient’s mouth. It was in table by the material (normal saline, sodium chloride, 0.9%), according to instructions of dental disease specialist. It was regarded as a natural model replica. It has been conducted two tests on some samples: studying the macroscopic damage for teeth and studying the influence compressibility for teeth. The design of generation argon plasma needle system, this system works on production Non- thermal plasma at atmospheric pressure, where used simples electronics constructions and cost low, it has power to generate high electric field on electrodes enough to ionize different gases and flow in atmospheric pressure. The device jet plasma needle used surely from no events any macroscopic or mechanical damage in build inside teeth (compressibility) ,where it applied on some teeth sample at time double treatment time ,then teeth check consequently favorableness result ,where load force of tooth without plasma exposure was 1.74kN while load force of tooth with plasma exposure was 1.824kN.Studying the macroscopic damage for teeth, the mentioned area were not affected with damage or change colors, therefore in effecting the teeth with any negative results during plasma needle process.